SURVEY TENTANG PENGGUNAAN BAHAN AJAR PADA MATA PELAJARAN PRODUKTIF AKUNTANSI DI KELAS X AKUNTANSI SMK NEGERI 1 LAMONGAN - KIKI MARLINDA A (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
Teaching materials is very important element that wasrequired teaching materials and decent standard. Teaching materials either to be in accord with standards appropriate teaching materials by bsnp namely the viability of contents, language, the presentation, and the graph. The aim is to find the teaching material used as teaching materials, and the election appropriate teaching material used for learning activities, and the response of the student teaching material. This research using a descriptive the quantitative study. Technical data is applicable in an interview that poll, and documentation. The results show (1) the teaching material used was teaching material printed in a book (the package. The reason is because the materials contained s considered most appropriate with our curriculum and comprehensible students. (2) any textbook subjects productive accounting improperly used for learning activities. (3) the students for using textbooks subjects productive accounting is good. Keywords : Teaching Materials, Feasibility, Response